Improved Upland Rice: Adaptability, Agronomic and Farmer Acceptability Assessment under Semi-Arid Conditions of South Western Uganda - Kankwatsa, Peace; Muzira, Robert; Mutenyo, Hellen; Lamo, Jimmy (Open Access Library Journal, 2019)
Enhancing the ability of plants to tolerate abiotic and biotic stresses is the current strategy for increasing agricultural productivity worldwide. Improved upland rice varieties characterized by early maturity, high disease resistance, high drought tolerance, high yielding potential, high grain quality and marketability are required by farmers to increase upland rice production to meet the increasing food and income demands. Improved and local upland rice varieties were evaluated across two seasons with and without fertilizer application. Insufficient soil water availability, low soil fertility and the blast disease were the major stresses that affected upland rice in the Rubirizi and Mitooma experimental sites in the South Western Agro Ecological Zone of Uganda. Integration of improved rice variety and soil fertility amendment with fertilizer plus proper crop management cultural practices resulted in high agronomic performance. Varieties NamChe 4, NamChe 5 and E22 showed superior performance over the other varieties in the field, and had significantly high probability (P ≤ 0.15) of being accepted by farmers. The early maturing NERICA 10, late maturing NERICA 6, SUPERICA 1 and Local Var., had high probabilities of being rejected because of low yielding, late maturity, drought intolerance, small panicle size, poor grain filling and high susceptibility to rice blast caused by Magnaporthe grisea . Therefore, improved varieties have great potential of increasing rice production in SWAEZ-Uganda, if farmers adopt the multi-technology integration approach.
Keywords: Upland Rice; Adaptability; Agronomic Performance; Variety Preference and Acceptability